2023
DOI: 10.1186/s42483-023-00161-5
|View full text |Cite
|
Sign up to set email alerts
|

3′ UTR is critical for viral RNA accumulation of jasmine virus H

Abstract: Jasmine virus H (JaVH) is a newly reported viral pathogen of jasmine in China and USA. To study the viral gene function and pathogenic mechanism, a full-length infectious clone of JaVH (pXT-JaVHFJ) was constructed under the control of the cauliflower mosaic virus 35S promoter. pXT-JaVHFJ induced a systemic infection in Nicotiana benthamiana plants by Agro-infiltration, which demonstrated that pXT-JaVHFJ was biologically active. Jasmine showed yellow spots after rubbing with total RNA extracted from Agro-infilt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Recently, Zhu et al. (2023) highlighted the importance of identified nucleotide differences in the 3′ UTR of genome RNA of two isolates of jasmine virus H ( Tombusviridae family) in the severity of symptoms and thus in the viral RNA accumulation (Zhu et al., 2023). In turn, Wang et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Zhu et al. (2023) highlighted the importance of identified nucleotide differences in the 3′ UTR of genome RNA of two isolates of jasmine virus H ( Tombusviridae family) in the severity of symptoms and thus in the viral RNA accumulation (Zhu et al., 2023). In turn, Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…A range of animal (e.g., dengue, sindbis, corona, polio) and plant (barley yellow dwarf, brome mosaic, turnip crinkle, tobacco mosaic, cowpea mosaic and alfalfa mosaic) viruses have been examined to highlight the role of 3′ UTR in the virus life cycle and as a potential target for pharmaceutical applications. These studies have shown that the changes in a sequence and thus in the structure of the 3′ UTR significantly affect viral virulence (Liu et al., 2020), accumulation and systemic infection (Alvarado‐Marchena et al., 2022; Wang et al., 2019; Xu et al., 2012; Zhu et al., 2023).…”
Section: Introductionmentioning
confidence: 99%